Control of Clostridium perfringens germination and outgrowth by buffered sodium citrate during chilling of roast beef and injected pork - Thippareddi, H.; Juneja, V.K.; Phebus, Randall K.; Marsden, James L.; Kastner, Curtis L. (My University, 2008)
Inhibition of the germination and outgrowth of Clostridium perfringens by buffered sodium citrate (Ional) and buffered sodium citrate supplemented with sodium diacetate (Ional Plus) during the abusive chilling of roast beef and injected pork was evaluated. Beef top rounds or pork loins were injected with a brine containing NaCl, potato starch, and potassium tetrapyrophosphate to yield final in-product concentrations of 0.85, 0.25, and 0.20%, respectively. Products were ground and mixed with Ional or Ional Plus at 0, 0.5, 1.0, and 2.0%. Each product was mixed with a three-strain C. perfringens spore cocktail to obtain final spore concentrations of ca. 2.5 log10 spores per g. Chilling of roast beef from 54.4 to 7.2°C resulted in C. perfringens population increases of 1.51 and 5.27 log10 CFU/g for 18- and 21-h exponential chill rates, respectively, while chilling of injected pork resulted in increases of 3.70 and 4.41 log10 CFU/g. The incorporation of Ional into the roast beef formulation resulted in C. perfringens population reductions of 0.98, 1.87, and 2.47 log10 CFU/g with 0.5, 1.0, and 2.0% Ional, respectively, over 18 h of chilling, while 1.0% Ional Plus was required to achieve similar reductions (reductions of 0.91 and 2.07 log10 CFU/g were obtained with 1.0 and 2.0% Ional Plus, respectively). An Ional or Ional Plus concentration of 1.0% was required to reduce C. perfringens populations in roast beef or injected pork chilled from 54.4 to 7.2°C in 21 h. Cooling times for roast beef or injected pork products after heat processing can be extended to 21 h through the incorporation of 1.0% Ional or Ional Plus into the formulation to reduce the potential risk of C. perfringens germination and outgrowth.
Keywords: Beef; Pork; Food safety; Clostridium perfringens; Sodium citrate